2010
DOI: 10.1136/jcp.2010.080713
|View full text |Cite
|
Sign up to set email alerts
|

Strong cytoplasmic expression of COX2 at the invasive fronts of gallbladder cancer is associated with a poor prognosis

Abstract: The IF of gallbladder cancer is characterised by significantly increased expression of p21, p53 and strong COX2 expression, and strong cytoplasmic COX2 expression at IF is associated with a poorer prognosis. Heterogeneity between TC and IF should be considered in in situ molecular studies, especially during interpretation of immunohistochemical stain results and tissue microarray construction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Among them, MMP2, MMP9, cyclooxygenase-2 (COX2), b-catenin, and urokinase plasminogen activator, are considered the primary tumor-invasive effectors (13,20,(37)(38)(39). In our study, we found that, after stimulation by EXO, expression of the mRNA levels of MMP2, MMP9, and COX2 was significantly elevated in 3LL and B16 tumor cells.…”
Section: Discussionsupporting
confidence: 50%
“…Among them, MMP2, MMP9, cyclooxygenase-2 (COX2), b-catenin, and urokinase plasminogen activator, are considered the primary tumor-invasive effectors (13,20,(37)(38)(39). In our study, we found that, after stimulation by EXO, expression of the mRNA levels of MMP2, MMP9, and COX2 was significantly elevated in 3LL and B16 tumor cells.…”
Section: Discussionsupporting
confidence: 50%
“…PTGS2 is not usually expressed in normal gallbladder epithelium but is apparent in dysplastic lesions, with increased expression in high-grade compared to low-grade lesions. Increased COX-2 expression is particularly common in samples with p53 overexpression [90,91]. Aspirin, a cyclooxygenase inhibitor, has been associated with a reduced risk of GBC [92], similar to what has been observed for colorectal cancer [93].…”
Section: Gallstone Disease Chronic Inflammation and Gallbladder Cancmentioning
confidence: 97%
“…30 Several cytokines, growth factors, and small molecules, such as TGF-b, TNF-a, and COX2, that are actively involved in the inflammatory response are deregulated in GBC and have been associated with malignant transformation of gallbladder epithelium. [31][32][33][34][35] As mentioned in the literature, CTGF may be differentially regulated by some components of the inflammatory process, contributing to pathogenesis in highly inflamed tissues. 27,36 We found that CTGF levels increase progressively from CC to advanced GBC, and, in a cancer-related inflammation context, it might be possible that complex interactions between crucial inflammatory mediators and CTGF in early stages of gallbladder carcinogenesis-in association with other carcinogenic stimuli-may contribute to the development of sequential histologic changes of the mucosal epithelium favoring the appearance of precursor lesions that ultimately lead to invasive carcinoma.…”
Section: Commentmentioning
confidence: 99%